Carbon Leakage with Structural Gravity - Rahel Aichele (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The future international climate policy architecture will most likely consist of partial climate policy initiatives like the EU's Emission Trading System. Trade integration threatens to undermine these systems' environmental effectiveness by shifting emissions to other countries. We estimate a gravity model based on 103 countries and use it to simulate several such climate policy experiments. The model's parameters are structurally linked to empirical estimates, i.e. bilateral trade costs and the elasticity of substitution are consistent with the data. Unlike previous empirical work, the approach allows to quantify emission relocation in general equilibrium. With trade liberalization experiments, the model also allows to deliver a perspective on environmental aspects of hypothetical FTA formation. We find that an EU emission allowance price of 15 US- suffi ces to bring the EU on track for its Kyoto target but also leads to emission relocations of about 10% of the EU's emission savings.
Keywords: F18; F47; Q54; 330